Quantification of Crack Formation Using Image Analysis and its Relationship with Permeability - Mihashi, H.; Ahmed, Shaikh; Mizukami, T.; Nishiwaki, T. (Aedificatio Publishers, 2006)
In this study a relationship between permeability of concrete and fractal dimension of crack is established. For this purpose four series of specimens of fiber reinforced cementitious composites are prepared. Specimens are subjected to uniaxial tension in order to create targeted damage (cracking) prior to permeability test. Image analysis is done on the cracked surface and fractal dimension of cracks are calculated using box counting method. Maximum crack width is found to have correlation with the coefficient of permeability. However, such correlation was observed neither between coefficient of permeability and crack area nor between coefficient of permeability and crack density. Relationships of fractal dimension of cracks is established with the maximum crack width, crack area and crack density. Trilateral relationship among coefficient of permeability, the maximum crack width and fractal dimension are established.